SPK Penentuan Asisten Dosen (Studi Kasus : Program Studi Sistem Informasi FMIPA UNTAN) - Fania Fania (Prosiding SISFOTEK, 2018)
Selected assistants greatly affect the sustainability and quality of student learning outcomes. The recipients of assistant lecturers conducted so far are solely based on the student’s wishes themselves without requirements how become a lecturer assistants. But sometimes it causes difficult problems to get the right assistant lecturer. Therefore it is necessary to have a DSS (Decision Support System) that can assist in determining the great decisions that can be targeted as assistant lecturers. The technique used is the Simple Additive Weighting (SAW) method which is part of the Muti-Attribute Decision Making (MADM) technique by performing weighted summing and ranking techniques for each best alternative. Used as a measure of suitability that corresponds to accurate data based on student history or notes.